2023
DOI: 10.1097/corr.0000000000002901
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Novel Tyrosine Kinase Fusion Genes as Potential Therapeutic Targets in Bone and Soft Tissue Sarcomas Using DNA/RNA-based Clinical Sequencing

Nobuhiko Hasegawa,
Takuo Hayashi,
Hidetaka Niizuma
et al.

Abstract: Background Approximately 1% of clinically treatable tyrosine kinase fusions, including anaplastic lymphoma kinase, neurotrophic tyrosine receptor kinase, RET proto-oncogene, and ROS proto-oncogene 1, have been identified in soft tissue sarcomas via comprehensive genome profiling based on DNA sequencing. Histologic tumor-specific fusion genes have been reported in approximately 20% of soft tissue sarcomas; however, unlike tyrosine kinase fusion genes, these fusions cannot be directly targeted in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The current study [3] demonstrated the effectiveness of tyrosine kinase inhibitors in treating patients who have advanced sarcomas with tyrosine kinase fusion genes. Nonetheless, we must exercise caution when thinking about the potential clinical benefits of this The opinions expressed are those of the writer, and do not reflect the opinion or policy of CORR ® or The Association of Bone and Joint Surgeons ® .…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…The current study [3] demonstrated the effectiveness of tyrosine kinase inhibitors in treating patients who have advanced sarcomas with tyrosine kinase fusion genes. Nonetheless, we must exercise caution when thinking about the potential clinical benefits of this The opinions expressed are those of the writer, and do not reflect the opinion or policy of CORR ® or The Association of Bone and Joint Surgeons ® .…”
mentioning
confidence: 66%
“…In this issue of Clinical Orthopaedics and Related Research ® , Hasegawa et al [3] presented results using a nextgeneration sequencing analysis of 82 patients with bone and soft tissue sarcomas. They detected potential fusion genes in 19% (11 of 58) of complex karyotype (nontranslocation-related) sarcomas.…”
mentioning
confidence: 99%